The Influence Of Rice Husk As Partial Replacement Material In Fired-Clay Brick - Johari, Izwan (2010)
The depletion of clay as a natural resource for making fired-clay bricks is in contrast with the high demand from the construction industry. This situation has obliged the researcher to introduce new construction materials using agricultural waste or to provide an alternative method to the manufacturing of traditional building material such as fired-clay brick, particularly during the current economic crisis. This thesis reports the effect on the usage of three types of rice husks as partial replacement material for clay in fired-clay brick. The investigation includes the manufacturing process, firing process, physical and mechanical testing and also the performance of fired-clay brick as masonry wall. Three types of fired-clay bricks with five different mix proportions (5-30%), including one type of control brick (0%), were produced using an extruder machine. In determining the optimum firing temperature, the control bricks were fired inside a muffle furnace with different temperatures ranging from 800-1250ºC. The optimum firing temperature was verified based on the controlled brick compressive strength result and used as the optimum firing temperature for the production of fired-clay bricks.